Sociocultural-Interactive Learning Strategies Employed by Students of Social Science and Engineering Studies - Yulianto Chandra (Institute of Research and Community Outreach - Petra Christian University, 2019)
This study aims to find how frequently employed are Sociocultural-Interactive (SCI) learning strategies by high-proficiency students of English for Academic Purpose at Petra Christian University in Surabaya, Indonesia. The study’s theoretical framework is from Oxford’s (2011) S2R Model. To know the employment frequency of the strategies, questionnaire was distributed to 33 students classified as high-proficiency students. These students were divided into two groups based on the fields of study: social science and engineering. Descriptive statistics was used to see which strategy is more frequently used. Furthermore, to see if there is a significant statistical difference between the two groups, Independent T Test was conducted. The findings suggested that although, in general, social science students used SCI strategies more frequently, there was no significant statistical difference between the two groups regarding their employment of the strategies. Additionally, the findings revealed the SCI strategies have not been maximally used in learning English. Keywords: learning strategies, sociocultural-interactive, high-proficiency, fields of study